Selection of optimum replacement option for amine pump in a gas processing plant using fuzzy analytical hierarchy process - Kassa, Freselam Mulubrhan; Gebremariam, M. A. (Journal of Critical Reviews, 2020)
In order to excel in the competitive market, it is essential to make a flawless decision which is difficult without considering different factors that affect it. These factors can be qualitative or quantitative which are full of uncertainties. Fuzzy analytical hierarch process (FAHP) is a very useful tool to model such a decision making process. In this study FAHP is used to select the optimum replacement option of amine pump in a gas processing plant. The gas processing plant has 10 unit of amine circulation pumps. These pumps have been installed since 1996. After installation, various problems occurred which lead to low reliability and availability of the amine pump system and a lot of design modification has been done since then. In this study three different replacement options are investigated to solve the problem. These options are a) To continue with the existing pump system through repair, b) To modify the existing system by changing one or two of the old pumps which has low performance by `a new one and c) To add a new pump. These options were assessed with four criteria; Ease of operation, Flexibility, Maintainability and environment. Data was collected from 25 employees and a pairwise comparison was conducted. It is found that the weight of the first option which is continuing with the existing system is higher with 0.47 values which show this option is preferable for the selected case. A sensitivity analysis is conducted to explore how the ranking of the analysis varies when the input data were changed.